Cosmetic facial massage - general and antistress rehabilitation - Badyin, I. Yu. (Journal of Education, Health and Sport, 2017)
The problem of preventing involutional skin changes remains one of the main issues in dermatological cosmetology. Cosmetic procedures are aimed at preventing age-related changes that arise as a result of the influence of various internal and external factors of aging, but the mechanisms of their correction are not sufficiently described.The influence of PRP (plate-enriched plasma) on the reparative and regenerative properties of the skin under the experimental modeling of dystrophic skin lesions was studied. In the framework of the experimental study, two series of experiments were conducted, namely: 60 mice to determine the characteristics of the pathology of the skin and 90 rats to study the pathogenesis of degenerative-dystrophic pathology of the spine. To achieve the purpose of the study in the experiment, the effectiveness of the use of autologous plasma and activated platelets on the experimental models of the corresponding pathology was determined.